Efeito de diferentes protocolos de ativação da solução irrigadora na limpeza das paredes e áreas de retenção de condutos radiculares - Dal’maso Taha, Silvia Wachmann (2020)
The objective of this study was to evaluate the effect of different protocols for activating the irrigating solution on cleaning the root canal. One hundred and sixty extracted bovine incisors were used, and on each side of its longitudinally cleaved roots, 2 different cleaning analyzes were performed. On one side, cleaning analysis was performed, using stereomicroscopy to observe the removal of debris in an internal groove created to simulate grooves in the root canal, being filled with dentin powder; on the other, smear layer removal was evaluated in the different thirds of the roots, using Scanning Electron Microscopy (SEM). Five cleaning protocols with 1% and 2.5% NaOCl were evaluated by the conventional irrigation technique (IC) or activated by: passive ultrasonic irrigation (PUI), continuous ultrasonic irrigation (CUI), passive ultrasonic irrigation with wireless ultrasonic device (UTX ) and low speed rotating plastic rod (ECL). The results showed that there were no significant differences in smear layer removal by different techniques, regardless of the third and NaOCl concentration. In the removal of dentin debris, conventional irrigation was surpassed by the other techniques of activation of the irrigating solution, both when using 1% and 2.5% NaOCl (Kruskal-Wallis and Student-Newman-Keuls, p <0 , 05). Thus, the analysis of the results suggests, when using concentrations of 1 and 2.5%, irrigation with NaOCl alone is not sufficient to remove the smear layer. However, its activation is important for cleaning larger debris from irregularities in the canal walls.